OPTIMALISASI STABILITAS PADA LAPIS ASPAL BETON DENGAN MENGGUNAKAN AGREGAT LIMBAH BETON - Aldo Verdiawan; Andri Dwi Cahyono; Evita Fitrianis Hidiyati; Aldo Riki Saputra; Rizky Hary Anto; Anggik Fatkhurrokhman; Mochammad Munhamir; Muhammad Bagus Maulana; Rendy Kurnia Dewanta (LPPM Universitas Abdurrab, 2023)
Concrete waste is waste material produced during the construction, renovation or demolition of concrete. The waste comes from residential areas that were evicted or demolished so that the airport land becomes sterile. The negative effects of the development, the large amount of concrete waste due to demolition and the absence of innovation in handling concrete waste. Therefore, utilizing concrete waste as a substitute for coarse aggregate in making marshal samples for asphalt road planning. so this research using materials from recycling rca concrete is very meaningful to determine which type of pavement to be used in the research. Therefore, to overcome these problems, the method used in this research is SNI 06- 2489- 1991 Procedures for Testing Asphalt Combinations with Marshall Equipment. By using RCA Waste coarse aggregate on the constituent materials of AC-BC concrete layer obtained an average stability result of 4843 kg. It is expected that these results are suitable for use as material to replace coarse aggregate on road pavements in accordance with the provisions of the 2018 bina marga specification.